1994
DOI: 10.2131/jts.19.supplementi_93
|View full text |Cite
|
Sign up to set email alerts
|

REPRODUCTIVE AND DEVELOPMENTAL TOXICITY STUDIES OF PACLITAXEL (III) : Intravenous administration to rats during the perinatal and lactation periods

Abstract: Paclitaxel, an antineoplastic agent, was administered intravenously to pregnant Crj: CD (SD) rats daily at dose levels of 0 (saline and vehicle), 0.1, 0.3 and 1.0 mg/kg from day 17 of gestation to postpartum day 21. Results were as follows: 1. The vehicle-treated group had no effect in any of the parameters that were measured in this study when compared to the saline-treated group. 2. 1.0 mg/kg paclitaxel caused suppression of the body weight gains associated with the decreased food consumption in F0 dams duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Paclitaxel administration in rats during early pregnancy can cause craniofacial malformations, diaphragmatic hernias, and kidney and cardiovascular system defects 70 . In advanced pregnancy, paclitaxel did not affect body weight, learning ability, and memory or spontaneous motor activity 71 …”
Section: Discussionmentioning
confidence: 99%
“…Paclitaxel administration in rats during early pregnancy can cause craniofacial malformations, diaphragmatic hernias, and kidney and cardiovascular system defects 70 . In advanced pregnancy, paclitaxel did not affect body weight, learning ability, and memory or spontaneous motor activity 71 …”
Section: Discussionmentioning
confidence: 99%
“…High doses of paclitaxel (10 mg/kg/day) applied during early pregnancy (day 8 of gestation) were associated with reduced litter size, reduction of fetal weight, malformations including craniofacial malformations, diafragmatic hernias, and defects of the kidneys, the cardiovascular system, and the tail [38]. In contrast, exposure to lower dosages of paclitaxel (1.0 mg/kg/day) prior to mating, during mating, in early and in advanced pregnancy revealed no significant influence on reproductive outcome and subsequent locomotor-, or neuro-development [39][40][41]. Similar results were observed in pregnant rats treated with carboplatin.…”
Section: Chemotherapy During Pregnancymentioning
confidence: 89%
“…The obtained results were consistent with those recorded by 9 who found that, cefeperazone depressed the uterine motility in two of six experiments while during pregnancy, they found that cefoperazone might not affected or depressed and/or stimulated the uterine motility. In other observation, cefepime had no effect on the delivery status of the offspring rats 16 , and 17 who found that, the spontaneous movement and tone of isolated uterus were not affected following cefbuperazone application.…”
Section: Discussionmentioning
confidence: 90%